2009
DOI: 10.1111/j.1365-2672.2009.04351.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of microbial source tracking methods in a Gulf of Mexico field setting

Abstract: Aims:  Microbial water quality and possible human sources of faecal pollution were assessed in a Florida estuary that serves shellfishing and recreational activities. Methods and Results:  Indicator organisms (IO), including faecal coliforms, Escherichia coli and enterococci, were quantified from marine and river waters, sediments and oysters. Florida recreational water standards were infrequently exceeded (6–10% of samples); however, shellfishing standards were more frequently exceeded (28%). IO concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 52 publications
2
26
2
Order By: Relevance
“…They measured fecal coliform rather than E. coli decay rates and found that this group declined more rapidly in marine sediments than in freshwater sediments; however, the differences were not as great as those observed in this study. Our field studies have shown that fecal coliform concentrations are frequently up to 2 orders of magnitude greater than E. coli concentrations in environmental waters, suggesting that some members of the larger group are better survivors in the secondary habitat than most E. coli strains (64)(65)(66)(67).…”
Section: Discussionmentioning
confidence: 99%
“…They measured fecal coliform rather than E. coli decay rates and found that this group declined more rapidly in marine sediments than in freshwater sediments; however, the differences were not as great as those observed in this study. Our field studies have shown that fecal coliform concentrations are frequently up to 2 orders of magnitude greater than E. coli concentrations in environmental waters, suggesting that some members of the larger group are better survivors in the secondary habitat than most E. coli strains (64)(65)(66)(67).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of esp fm was correlated with human polyomaviruses in polluted surface waters in Florida (227) and with fecal coliforms in another study (197). It has also been used in field studies in Florida, the Great Lakes, and Australia (5,39,196,209). A quantitative PCR (qPCR) method for esp fm has been developed and used in field studies in Australia (4).…”
Section: Microbial Source Trackingmentioning
confidence: 99%
“…Before filtration, sediment samples were weighed and diluted 1:10 (wt/vol) in sterile buffered water (20) and sonicated for 30 s at 14 W (sonic dismembrator model 100; Fisher Scientific) to dislodge bacterial particles attached to the sediment for the direct effect microcosms (1,29). For the indirect effect experiment, sediment samples were shaken for 2 min instead of being subjected to sonication (8).…”
Section: Direct Effect Experimentmentioning
confidence: 99%